Validity of Lepadichthys misakius (Tanaka 1908) and redescription of Lepadichthys frenatus Waite 1904 (Gobiesocidae: Diademichthyinae) - Fujiwara, Kyoji; Motomura, Hiroyuki (Zootaxa, 2019)
The clingfishes Lepadichthys frenatus Waite 1904 and Lepadichthys misakius (Tanaka 1908) are both redescribed as valid species, although the latter has previously been regarded as a junior synonym of the former. Lepadichthys frenatus and L. misakius are easily distinguished from their congeners by the following combination of characters: 14–19 dorsal-fin rays; 12–14 anal-fin rays; disc size moderate, its length 15.1–20.8 % of standard length (SL); and dorsal, anal and caudal fins connected by membranes. Lepadichthys misakius can be distinguished from L. frenatus by having 25–28 (modally 26 or 27) pectoral-fin rays [vs. 27–29 (29) in L. frenatus]; the upper end of the gill membrane level with the 5th to 8th (usually 6th) pectoral-fin ray base in lateral view [vs. 6th to 8th (7th)]; the lower 8th to 11th (9th) pectoral-fin ray base attached to the disc base by membrane [vs. 10th to 12th (11th)]; 7–11 (9) gill rakers on each arch [vs. 11–14 (12)]; anterior, posterior and least interorbital widths 9.0–11.8 (mean 10.7), 13.4–16.9 (15.3) and 3.2–8.8 (6.2) % SL, respectively [vs. 8.4–10.2 (9.4), 12.1–14.7 (13.5) and 2.8–5.9 (4.8) % SL, respectively]; and NC2 (nasal canal pore) usually located between the anterior and posterior margins of the posterior nostril (vs. usually located before the posterior nostril anterior margin). Morphological changes with growth of the two species are described in detail and a lectotype designated for L. frenatus.